A Ferrotoroidic Candidate with Well‐Separated Spin Chains. Issue 12 (11th February 2022) - Zhang, Jun; Wang, Xiancheng; Zhou, Long; Liu, Guangxiu; Adroja, Devashibhai T.; da Silva, Ivan; Demmel, Franz; Khalyavin, Dmitry; Sannigrahi, Jhuma; Nair, Hari S.; Duan, Lei; Zhao, Jianfa; et al.
Abstract: The search of novel quasi‐1D materials is one of the important aspects in the field of material science. Toroidal moment, the order parameter of ferrotoroidic order, can be generated by a head‐to‐tail configuration of magnetic moment. It has been theoretically proposed that 1D dimerized and antiferromagnetic (AFM)‐like spin chain hosts ferrotoroidicity and has the toroidal moment composed of only two antiparallel spins. Here, the authors report a ferrotoroidic candidate of Ba6 Cr2 S10 with such a theoretical model of spin chain. The structure consists of unique dimerized face‐sharing CrS6 octahedral chains along the c axis. An AFM‐like ordering at ≈10 K breaks both space‐ and time‐reversal symmetries and the magnetic point group of mm ′2′allows three ferroic orders in Ba6 Cr2 S10 : (anti)ferromagnetic, ferroelectric, and ferrotoroidic orders. Their investigation reveals that Ba6 Cr2 S10 is a rare ferrotoroid ic candidate with quasi 1D spin chain, which can be considered as a starting point for the further exploration of the physics and applications of ferrotoroidicity. Abstract : Ferrotoroidic order is one of the four primary ferroic order forms. Ba6 Cr2 S10 is reported to be a rare ferrotoroidic candidate with well‐separated 1D spin chain, where the spins are dimerized and antiferromagnetic‐like coupled and the toroidal moment is composed of only two antiparallel spins.